The kantian concept of Citizenship - Carrillo Castillo, Lucy (Estudios de Filosofía, 2010)
In the prologue to Fundamental Principles of the Metaphysics of Morals Kant brings to notice the difference between a reflection on the Fundamental Principles of Morale and the idea of how to “apply” the Principle of Morality to the everyday life of humans. According to his own point of view, the question on how to implement Morale in practical life supposes the necessity of adopting the perspective of a Pragmatic Anthropology. In this sense, the object of this essay is to make a Pragmatic Reading of the Kantian concept of Citizenship, with which one can better understand his conviction that the political should be constructed on the basis of Morale: the respect for Human Dignity. This pragmatic point of view will enable me to clarify: a) why Kant thinks that the grave difficulties of Politics reside in the task of knowing and being able to establish the necessary measures to guaranty the respect for Fundamental Rights, and b) in what manner the Kantian concept of Citizenship lays the foundations of the idea of Mutual Recognizance of Rights and Obligations. Due to this I divide the essay in three parts: 1) The ideas of Human Rights and Citizen Rights, and the concept of Cosmopolitan Right. 2) The concept of Citizenship in the light of his concept of a Republican State; and 3) how the notion of Citizenship was conceived by Kant for simple people, with a Common Sense.